Perceptions and plans for prevention of Ebola: results from a national survey. (December 2015) - Kelly, Bridget; Squiers, Linda; Bann, Carla; Stine, Alexander; Hansen, Heather; Lynch, Molly
Abstract Background Literature suggests that Americans may have higher levels of perceived threat to Ebola than are warranted. Methods We surveyed 1018 U.S. adults from a nationally representative Internet panel about their knowledge, perceived threat, and behavioral intentions during the 2014 Ebola outbreak. Results Eighty-six percent of respondents knew that Ebola could be transmitted through blood and bodily fluids. However, a large percentage had some inaccurate knowledge and 19 % believed Ebola would spread to the U.S. Respondents favored mandatory quarantine (63 %) and travel bans (55 %). Confidence in the ability of the media and government to accurately report on or prevent a U.S. epidemic was low. Fifty-two percent intended to engage in behaviors such as avoiding public transportation. Discussion Despite low perceived susceptibility, half intended to engage in behaviors to prevent transmission and large numbers favored policies not currently recommended by health officials. The extreme nature of Ebola virus likely motivated people to engage in behaviors and favor policies that were not necessary given the low risk of transmission in the U.S. Conclusions Health officials should ensure the public has accurate information about Ebola and bolster confidence in the government's ability to control infectious diseases in case of a future outbreak in the U.S.